Prediksi Jumlah Keterserapan Mahasiswa Baru di Perguruan Tinggi Negeri Menggunakan Metode Monte Carlo - Widiandana, Panggah; Aulia, Muhammad Immawan; Srimulyani, Wahyu; Pratama, Rizky Andhika; Aryana, Vendi Alif Putra (Universitas Muhammadiyah Sorong, 2023)
The increasing number of new state university students requires serious attention in planning admissions. Strategic decisions about campus capacity, facilities and infrastructure, and study programs must be carefully considered to accommodate the demand for new students efficiently. This study aims to develop a predictive model for new students' absorption in public universities by utilizing the Monte Carlo method. The absorption of new students is an important indicator in evaluating the quality and attractiveness of a tertiary institution. Using the Monte Carlo technique to predict the absorption of new students at state universities using the Monte Carlo method, predictions for the next five years are obtained with a total absorption of 27.6 and the Monte Carlo method can help evaluate private universities in filling out the feasibility study section. Predicting student absorption in PTN using the Monte Carlo Method is very important to see opportunities for prospective study programs